Effect of Cropping Pattern and Fertilizer Dose Applied in Raised-Bed on The Growth and Yield of Rice (Oryza sativa L.) in Sunken-Bed of The Surjan Rice Field - Damar Suryaningndari; Didik Indradewa; Budiastuti Kurniasih; Endang Sulistyaningsih (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Surjan system (alternating bed system) is an agricultural system that combines dry and wet bedding system. It integrates food crop culture in the sunken-bed and annual crops in the raised-bed of the rainfed rice field. In Bantul, farmers commonly apply Surjan system in rice field by growing shallot (Allium cepa L. aggregatum group) and chili (Capsicum annuum L.) in the raised-bed, whereas no crop is grown in the sunken-bed. This present experiment evaluated the utilization of the sunken-bed for rice cultivation by utilizing fertilizer runoff from the raised-bed. Rice plants in the sunken-bed were not fertilized due to the expectation that it could utilize the fertilizer runoff from the raised-bed. The cropping pattern and the fertilizer dose in the raised-bed are suspected to affect the growth and yield of rice in the sunken-bed. The purpose of this study was to determine the effect of cropping pattern and fertilizer dose applied in raised-bed on the growth and yield of rice in sunken-bed of the Surjan rice field. This study were laid out in a split plot design with three replication. The main plot consists of two cropping pattern, namely shallot monoculture and intercropping shallot with chili. The fertilizer dose applied in raised-bed, namely 100% farmer's habit; 50% farmer’s habit; and 25% farmers' habit, occupying the sub plot. Dose of fertilizer applied in riased- bed according to the farmer's habit in research locatin is 622 kg NPK/ha (16-16-16) ; 228 kg ZA/ha and 76 kg KCl/ha. The results showed that there was no interaction between the cropping pattern and the fertilizer dose applied in the raised-bed on the growth and yield of rice in the sunken-bed. Compared with shallot monoculture, intercropping shallot with chili in raised-bed decreased the growth of rice in the sunken-bed. Compared with the 100% fertilizer dosage of farmer's habits, the fertilizer dose of 50% of the farmer's habits in the raised-bed increased the growth of rice in the sunken-bed. Cropping pattern and fertilizer dose in the raised-bed did not significantly affect the rice yield grown in the sunken-bed of the Surjan rice field.